PP.56 Abnormal Placental Pathology and Short-Term Neonatal Outcomes in the Preterm Infant. (26th April 2013) - Bonney, EA; Browne, HE; Barrett, L; Coulter, C; Morris, J; Greenwood, DC; Stahlschmidt, J; Walker, JJ; Simpson, NAB
Abstract : Introduction: Placental pathology provides a unique insight into the intrauterine environment prior to preterm birth. Objectives: To investigate correlations between maternal variables and abnormal placental pathology in a cohort of women delivering extremely preterm; to determine associations between these and the incidence of adverse short-term neonatal outcome. Method: Placental histopathology reports from women who gave birth in Leeds between 22–32 weeks gestation from 2009–2011 were obtained. Relevant maternal and neonatal data were accessed. Intergroup differences and trends were sought using Mann-Whitney U and logistic/linear regression analyses where appropriate. Results: 269 women were included in the study. 89% of the placentas demonstrated abnormal pathology (infection/inflammation and/or ischaemia/infarction). Smoking and socioeconomic deprivation were associated with an increased incidence of placental infection (p = 0.02) and ischaemia (p = 0.0001). Babies were born significantly earlier if their placenta demonstrated infection than those whose showed ischaemia (p = 0.0001). Neonates born with infected placentas tended to be more likely to have intraventricular haemorrhage than those with ischaemic placentas (adjusted OR 1.9; 95th CI 0.5–6.5, p = 0.3). Conclusion: Intrauterine infection/inflammation is the predominant antecedent of extreme prematurity, and is associated with maternal smoking and socioeconomic deprivation. Further studies need to consider the mechanisms which link these features. (supported by Cerebra)